THE BALLET MUSIC AS A MEANS OF INSTRUMENTAL AND PERFORMING TRAINING OF THE FUTURE TEACHER (Pedagogy of Higher and Secondary Education, 2007)
In the article by the necessity c f the usage of the ballet music is grounded considered in the piano playing teaching of the students of the Department of Art of the Pedagogical University.
Keywords: instrumental and performing training; integrative approach; ballet music